Immobilized synthetic pathway for biodegradation of toxic recalcitrant pollutant 1,2,3-trichloropropane - Dvorak, Pavel; Bidmanova, Sarka; Damborsky, Jiri; Prokop, Zbynek (Environmental science & technology, 2014)
The anthropogenic compound 1,2,3-trichloropropane (TCP) has recently drawn attention as an emerging groundwater contaminant. No living organism, natural or engineered, is capable of the efficient aerobic utilization of this toxic industrial waste product. We describe a novel biotechnology for transforming TCP based on an immobilized synthetic pathway. The pathway is composed of three enzymes from two different microorganisms: engineered haloalkane dehalogenase from Rhodococcus rhodochrous NCIMB 13064, and haloalcohol dehalogenase and epoxide hydrolase from Agrobacterium radiobacter AD1. Together, they catalyze consecutive reactions converting toxic TCP to harmless glycerol. The pathway was immobilized in the form of purified enzymes or cell-free extracts, and its performance was tested in batch and continuous systems. Using a packed bed reactor filled with the immobilized biocatalysts, 52.6 mmol of TCP was continuously converted into glycerol within 2.5 months of operation. The efficiency of the TCP conversion to the intermediates was 97%, and the efficiency of conversion to the final product glycerol was 78% during the operational period. Immobilized biocatalysts are suitable for removing TCP from contaminated water up to a 10 mM solubility limit, which is an order of magnitude higher than the concentration tolerated by living microorganisms.
Keywords: chemické látky znečišťující vodu; Biocatalysis; Biodegradation, Environmental; Biotransformation; Bioreactors; propan; Water Pollutants, Chemical; Hydrolases; hydrolasy; Propane; bioreaktory; Rhodococcus; Time Factors; biotransformace; enzymy imobilizované; metabolické sítě a dráhy; Agrobacterium; časové faktory; biokatalýza; Enzymes, Immobilized; Metabolic Networks and Pathways; biodegradace